4CPS-097 Extended versus standard cytomegalovirus prophylaxis in solid organ transplantation. (2nd March 2018) - Serrano, M; Guillen-Grima, F; Martin-Moreno, P; Rabago, G; Garcia-del-Barrio, M; Reina, G; Fernandez-Alonso, M; Herrero, JI
Abstract : Background: Cytomegalovirus (CMV) is the most important viral pathogen in solid organ transplant (SOT) recipients. Prolongation of CMV prophylaxis from 3 to 6 months has been associated with a long-term reduction in CMV infection in high-risk renal recipients It has been recommended in this group of patients and, by extension, in other SOT recipients. Purpose: To assess the efficacy and safety of CMV prophylaxis in SOT recipients, as well as comparing the efficacy of extended versus standard CMV prophylaxis. Material and methods: Cases of SOT patients from 2007 to 2014 were retrospectively studied. Patient demographics, transplant type, donor and recipient CMV serostatus, immunosuppressive therapy and data of CMV prophylaxis were collected from electronic patient files. CMV replication after prophylaxis was monitored according to SOT protocols (at least monthly from 3 to 6 months after SOT, and then when clinically indicated). CMV infection after prophylaxis was reviewed in order to evaluate the efficacy of prophylaxis. Outcome was compared between the groups of patients with standard prophylaxis (length <100 days) and extended prophylaxis (>100 days). Safety analysis was based on the evaluation of myelotoxicity, according to the National Cancer Institute Common Toxicity Criteria scale Version 4. 0. Results: Of the 438 SOT patients, 60 (13.7%) received CMV prophylaxis (37 renal, 15 hepatic and eight cardiac) for a median of 122 days. The main CMV serostatus was D+/R- (70.0%). Thirty-four of the 60 patients (56.7%) received extended prophylaxis. After a mean of 48 months of follow-up, 16 patients (26.7%) developed CMV infection after the end of prophylaxis (10 asymptomatic infections, two viral syndromes and four invasive diseases). Mean time to CMV replication was 52 days. Extended prophylaxis was not associated with fewer CMV infections (26.9% vs. 26.5% with standard prophylaxis). Thirty (50%) patients developed haematological toxicity, mainly neutropaenia (38.3%). Length of prophylaxis was independently associated with toxicity (OR 1.01, 95% CI: 1.00 to 1.02, p<0.05). Conclusion: Extended CMV prophylaxis did not reduce the CMV infection rate after prophylaxis. Haematological toxicity during tprophylaxis was common and it was associated with length of therapy. We cannot recommend extended CMV prophylaxis as a general rule in high-risk SOT recipients. Reference and/or Acknowledgements: 1. Humar A, et al. Transplantation2010;90:1427–1431. No conflict of interest